Analisis Kemandirian Otonomi Daerah: Kasus Kota Malang (1999 - 2004) - Hadi Sumarsono (Universitas Negeri Malang, 2009)
One way to assess the capability of an autonomous region in implementing its autonomy is by measuring the performance of the region in managing decentralized fiscal and the degree of inde-pendency toward the central government. There are six main variables which considered being the performance indicators of the capability: fiscal need, fiscal capacity, fiscal effort, degree of fiscal decentralization, and elasticity coefficient of PAD (regional revenue) compared to PDRB. By ana-lyzing panel data from 1999 to 2004 of Malang City, this simple empirical research shows that ef-ficiency in public finance is relatively high, while trend of PAD toward PDRB is inelastic. This means that in the long run Malang City will have some degree of a positive trend of PAD and PDRB growth if the government could maintain the independency policy in terms of preference to local investment incentives.Keywords: regional autonomy, regional finance, regional revenue, fiscal decentralization and independency policy__________________________________________________________________________________________